Night Sky of the Flint Hills - Fred Gassert (Symphony in the Flint Hills, 2012)
While enjoying the Flint Hills during the day, it is the vast openness that first strikes the observer. There is literally nothing for miles and miles. But when the sun goes down, one experiences something that is awe-inspiring.
Keywords: night; sky; Flint Hills; shadow; darkness; peace; pleasant; moon; stars; clear; summer; galaxy